2016
DOI: 10.1186/s12913-016-1419-1
|View full text |Cite
|
Sign up to set email alerts
|

The Youth Health Care measure-satisfaction, utilization, and needs (YHC-SUN)-development of a self-report version of the Child Health Care (CHC-SUN) proxy-measure

Abstract: BackgroundThe transition of health care of youth (age 15–25) with chronic conditions requires the assessment of adolescents’ access, use and needs as well as satisfaction with the health services they use. The aim of this study was to test the adolescent adaptation of the parent version “Child Health Care Questionnaire - Satisfaction, Utilization and Needs” (CHC-SUN) concerning its psychometric performance and appropriateness for adolescents and young adults.MethodsThe Youth Health Care Measure (YHC-SUN) was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 30 publications
4
24
0
Order By: Relevance
“…These results point to the need for other sudies to investigate more thoroughly the non-medical mechanism of the health services use in order to provide important information to policy makers. However, the value of the utilization of the GP or FP in our survey is in accordance with the values found in a study conducted in Germany (68.3%) among younger adolescents [ 28 ] and in a survey conducted in Canada among adolescent and young adults. The latter found 67.1% of adolescents between 12 to 14 year olds and 69.8% between 15 to 19 year olds had used their family pediatrician in the last 12 months [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results point to the need for other sudies to investigate more thoroughly the non-medical mechanism of the health services use in order to provide important information to policy makers. However, the value of the utilization of the GP or FP in our survey is in accordance with the values found in a study conducted in Germany (68.3%) among younger adolescents [ 28 ] and in a survey conducted in Canada among adolescent and young adults. The latter found 67.1% of adolescents between 12 to 14 year olds and 69.8% between 15 to 19 year olds had used their family pediatrician in the last 12 months [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…The parent-reported instrument we used has since been modified for self-report in German-speaking youth, based on a mixed sample of 182 chronically ill adolescents including 28 patients with gastrointestinal (GI) disease. 38 In this study, 36% of patients in the GI group reported unmet needs relating to school or work, which was more than for any of the other disease groups (diabetes, multiple sclerosis, arthritis, skin disease, pulmonary conditions). With respect to the CHC-SUN, as in our survey, the school services subscore was lowest as compared with other domains in all patient groups, but in particular so for GI diseases.…”
Section: Discussionmentioning
confidence: 53%
“…Satisfaction with health care was measured on a general level by the Customer Satisfaction Questionnaire (CSQ-4) [ 22 ] and on a domain-specific level with a modified short-form of the Youth Health Care – Satisfaction, Utilization and Needs (YHC-SUN-SF) measure [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…YHC-SUN-SF comprises two modules: a module covering “provision of health care services” and a module covering “satisfaction with health care”. Later, a self-reported version for adolescents “The Youth Health care measure - Satisfaction, utilization, and needs (YHC-SUN)” was developed [ 23 ] as well as short-forms of both versions (CHC−/ YHC-SUN-SF).…”
Section: Methodsmentioning
confidence: 99%